The network society - van Dijk, Jan (London : SAGE Publications Ltd, 2020)
The Network Society is the essential guide to the past, consequences and future of digital communication, and forms a comprehensive introduction to how new media functions in contemporary society. New to this edition: {u2003}{u2022}{u2003}Renewed focus on the digital media economy, including examples, cases and real-world applications {u2003}{u2022}{u2003}New coverage of disinformation and fake news, including deep fake videos {u2003}{u2022}{u2003}Expanded treatment of the data economy, artificial intelligence, big data, robotics, and the economy and regulation of the Internet {u2003}{u2022}{u2003}Updates to the story of digital youth culture, as a foreshadow of future new media use Clear and engaging, this is a vital guide for digital and new media students seeking to understand a diverse, fast-moving field.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Digital communications; Digital media